2011
DOI: 10.1111/j.1469-185x.2011.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Shifting species interactions in terrestrial dryland ecosystems under altered water availability and climate change

Abstract: Species interactions play key roles in linking the responses of populations, communities, and ecosystems to environmental change. For instance, species interactions are an important determinant of the complexity of changes in trophic biomass with variation in resources. Water resources are a major driver of terrestrial ecology and climate change is expected to greatly alter the distribution of this critical resource. While previous studies have documented strong effects of global environmental change on specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
140
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 162 publications
8
140
1
1
Order By: Relevance
“…Experiments and syntheses conducted in recent years have projected modifications and disruptions in species and multi-trophic interactions in drylands [61,68]. The complexities in the responses of organisms to global change challenge the establishment of general predictions.…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments and syntheses conducted in recent years have projected modifications and disruptions in species and multi-trophic interactions in drylands [61,68]. The complexities in the responses of organisms to global change challenge the establishment of general predictions.…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…The dryland biota in general is known to be well-adapted to infrequent, intense and unpredictable pulses of precipitation [4]. However, increasing temperatures and prolonged drought events associated with global change will pose physiological water balance challenges to a wide suite of organisms, including birds [60], reptiles [61] and insects [62], as transpiration increases. Expected changes in temperature and rainfall frequency may even promote extreme mortality events, as recently recorded in organisms as disparate as small birds [63] and mosses [64].…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…Water availability probably has both bottom-up and top-down effects on food webs [9], but evidence for top-down effects comes mostly from observational research [5,[10][11][12], limited field manipulations [13,14] or cage experiments [15]. This evidence suggests that consumers may meet water demands by consuming large amounts of moist food when environmental water sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that water balance can influence consumption of moist food for particular consumers [9,15]. We hypothesized that this alteration of consumption would lead to changes in the strength of top-down effects in real food webs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation